2009
DOI: 10.1186/1471-2334-9-14
|View full text |Cite
|
Sign up to set email alerts
|

Improving survey methods in sero-epidemiological studies of injecting drug users: a case example of two cross sectional surveys in Serbia and Montenegro

Abstract: BackgroundLittle is known about the prevalence of HIV or HCV in injecting drug users (IDUs) in Serbia and Montenegro. We measured prevalence of antibodies to HIV (anti-HIV) and hepatitis C virus (anti-HCV), and risk factors for anti-HCV, in community-recruited IDUs in Belgrade and Podgorica, and determined the performance of a parallel rapid HIV testing algorithm.MethodsRespondent driven sampling and audio-computer assisted survey interviewing (ACASI) methods were employed. Dried blood spots were collected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
(51 reference statements)
0
18
0
Order By: Relevance
“…A study among 600 PWID in Odessa, Ukraine found that police beatings were common, with nearly 50% reporting at least one such experience 20 119. Studies in other regions also suggest relatively high rates of police arrest (42–76% ever having been arrested) 18 27 107 120. In Estonia and Lithuania, an estimated 58–70% of PWID had been in prison at least once 74.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study among 600 PWID in Odessa, Ukraine found that police beatings were common, with nearly 50% reporting at least one such experience 20 119. Studies in other regions also suggest relatively high rates of police arrest (42–76% ever having been arrested) 18 27 107 120. In Estonia and Lithuania, an estimated 58–70% of PWID had been in prison at least once 74.…”
Section: Resultsmentioning
confidence: 99%
“…In Estonia and Lithuania, an estimated 58–70% of PWID had been in prison at least once 74. In Georgia and Russia, this figure was between 6% and 37%,18 52 64 65 79 121 122 In Central Europe, between 18% and 50% of respondents report previously having been in prison 93 107…”
Section: Resultsmentioning
confidence: 99%
“…Despite only one HIV case found in the study, the growing presence of HCV may also have long-term implications for the emergence of other blood-borne infections, including HIV. The comparison between the 2 study waves is limited, however, because the 2005 prevalence was a population-level estimate for the city of Podgorica [11] while this study included participants from across Montenegro. …”
Section: Discussionmentioning
confidence: 99%
“…We selected the covariates that were found to be associated with positive anti-HCV status in a comparable study of IDUs in Montenegro carried out in 2005 [11]. These variables were: frequency of injecting, ever having injected with used needles or syringes, being arrested in the past 12 months, age at first injection and ever having been tested for HCV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation